2022
DOI: 10.3390/nu14061284
|View full text |Cite
|
Sign up to set email alerts
|

β-Carotene Supplementation and Risk of Cardiovascular Disease: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: β-carotene is widely available in plant-based foods, while the efficacy of β-carotene supplementation on cardiovascular disease (CVD) risk remains controversial. Hence, we performed a systematic review and meta-analysis on randomized controlled trials to investigate the associations between β-carotene supplementation and CVD risk as well as mortality. We conducted literature searches across eight databases and screened the publications from January 1900 to March 2022 on the topic of β-carotene treatments and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 39 publications
0
19
1
Order By: Relevance
“…62-0.87), 29 while a meta-analysis of RCTs suggested that β-carotene supplementation slightly increased CVD risk (RR: 1.04; 95% CI: 1.00, 1.08). 30 In our study, the association between carotenoids and CVD was not verified in NHANES. This might be explained by the different dietary intake of Chinese and American populations.…”
Section: Papercontrasting
confidence: 73%
“…62-0.87), 29 while a meta-analysis of RCTs suggested that β-carotene supplementation slightly increased CVD risk (RR: 1.04; 95% CI: 1.00, 1.08). 30 In our study, the association between carotenoids and CVD was not verified in NHANES. This might be explained by the different dietary intake of Chinese and American populations.…”
Section: Papercontrasting
confidence: 73%
“…Diet rich in β-carotene has been found to be preventive for heart-related problems (Yang et al 2022 ). The pigment is fat-soluble and is transported primarily in low-density lipoproteins (LDL).…”
Section: Discussionmentioning
confidence: 99%
“…hand, the benefits of carotenoid intake in reducing the risk of CVD are well known, but not when they are present in orange fruits or their products. 6,[45][46][47] Blond oranges usually contain xanthophylls (e.g., violaxanthin and zeaxanthin), but the presence of carotenes (e.g., lycopene and β-carotene) is an unusual feature in orange fruits. Brasili et al 25 identified 403.2 µg and 312.5 µg of xanthophylls in BOJ and CCOJ, respectively.…”
Section: Food and Function Papermentioning
confidence: 99%